Seed Distribution Report in Makueni, Kitui and Taita Taveta Counties - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The AICCRA project distributed 9.16 tons of improved drought-tolerant seed varieties of sorghum, pearl millet, green gram and finger millet to 4,650 farmers in Makueni, Kitui and Taita Taveta Counties during the March-April-May 2024 ‘long rains’. Among the beneficiaries, 66% were women farmers. The seed distribution, conducted in collaboration with the county extension officers and Trainer of Trainers (ToTs) at each ward, aimed to enhance agricultural productivity. This distribution targeted new farmers who had not previously received seeds in the previous growing seasons under the AICCRA project, ensuring a wider reach.